Multi-walled carbon nanotubes: innovativesorbents for pre-concentration of polychlorinatedbiphenyls in aqueous environments - Ndunda, Elizabeth N.; Mizaikoff, Boris (Royal Society of Chemistry, 2015)
Carbon nanotubes (CNTs) have demonstrated outstanding chemical and mechanical stability, electricalproperties, and strong interactions with aromatic compounds owing to thep-electron system on thegraphene sheets. Taking advantage of these unique properties, we have developed a fully validatedsample pre-concentration technique for determination of polychlorinated biphenyls (PCBs) in aqueousenvironments using gas chromatography combined with a micro-cell electron capture detector (GC-mECD). The optimized method using pristine MWCNTs gave recoveries in the range of 46.0–92.5%,51.4–91.5%, 48.7–77.8% for tap water, river water, and lake water, respectively. Compared toconventional C18 adsorbent and oxidized MWCNTs (oMWCNTs), pristine MWCNTs provided the bestrecoveries, thereby confirming that MWCNTs are excellent alternatives for C18, with the ability toachieve high performance. The developed protocol achieved method detection limits in the range of0.002–0.011mgL 1and relative standard deviation (RSD) < 15.5%.